Robust ecological drought projections for drylands in the 21st century. (27th April 2020) - Bradford, John B.; Schlaepfer, Daniel R.; Lauenroth, William K.; Palmquist, Kyle A.
Abstract: Dryland ecosystems may be especially vulnerable to expected 21st century increases in temperature and aridity because they are tightly controlled by moisture availability. However, climate impact assessments in drylands are difficult because ecological dynamics are dictated by drought conditions that are difficult to define and complex to estimate from climate conditions alone. In addition, precipitation projections vary substantially among climate models, enhancing variation in overall trajectories for aridity. Here, we constrain this uncertainty by utilizing an ecosystem water balance model to quantify drought conditions with recognized ecological importance, and by identifying changes in ecological drought conditions that are robust among climate models, defined here as when >90% of models agree in the direction of change. Despite limited evidence for robust changes in precipitation, changes in ecological drought are robust over large portions of drylands in the United States and Canada. Our results suggest strong regional differences in long‐term drought trajectories, epitomized by chronic drought increases in southern areas, notably the Upper Gila Mountains and South‐Central Semi‐arid Prairies, and decreases in the north, particularly portions of the Temperate and West‐Central Semi‐arid Prairies. However, we also found that exposure to hot‐dry stress is increasing faster than mean annual temperature over most of these drylands, and those increases are greatest in northern areas. Robust shifts in seasonal drought are most apparent during the cool season; when soil water availability is projected to increase in northern regions and decrease in southern regions. The implications of these robust drought trajectories for ecosystems will vary geographically, and these results provide useful insights about the impact of climate change on these dryland ecosystems. More broadly, this approach of identifying robust changes in ecological drought may be useful for other assessments of climate impacts in drylands and provide a more rigorous foundation for making long‐term strategic resource management decisions. Abstract : Assessing climate change impacts in drylands is difficult because drought conditions are complex and not easily estimated from climate conditions alone and because long‐term precipitation projections vary substantially. Here, we constrain this uncertainty by identifying changes in ecologically relevant drought conditions that are robust across climate models. Results differ among drought types, with chronic drought stress increasing most in southern drylands and exposure to hot‐dry stress increasing fastest in northern drylands. These results illustrate how focusing on robust changes can provide a rigorous foundation for making long‐term strategic resource management decisions.